Evaluation of Antioxidant Activity of Vernonia amygdalina Leaves and Its Flavonoid-Phenolic Content - Muammar Fawwaz; Mamat Pratama; Musafira Musafira; Indira Wahab; Rina Iriani; Aminah Aminah; Andi Trihadi Kusuma; Muhammad Ikhlas Arsul (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Bitter leaf, Vernonia amygdalina (VA), is used in various alternative medicine in several countries,including Indonesia. This study aims to evaluate the antioxidant activity of VA leaves by three differentin vitro methods. The antioxidant activity was evaluated by radical scavenging of 1,1-diphenyl-2-picryl-hydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and cupric reducing antioxidantcapacity (CUPRAC). The antioxidant capacity by FRAP and CUPRAC methods were expressed asmg of quercetin equivalents (QE) per g extract (mgQE/g) and mg of ascorbic acid equivalents (AAE)per g extract (mgAAE/g), respectively. All methods were measured by UV-Visible spectrophotometryat maximum wavelength. The results exhibited that VA leaves ethanolic extract contains flavonoidphenolic.The VA leaves ethanolic extract has an antioxidant activity by scavenging the DPPH methodwith the half inhibition concentration (IC50) was 8,22 μg/mL. The antioxidant capacity of VA leavesethanolic extract by FRAP and CUPRAC methods was 21,03 mgQE/g and 160,64 mgAAE/g extract,respectively. The VA leaves ethanolic extract has a powerful antioxidant potency which might correlateto the flavonoid-phenolic content in the extract.